2017
DOI: 10.1002/tie.21946
|View full text |Cite
|
Sign up to set email alerts
|

International acquisitions and emerging market firms' performance—a structural contingency perspective

Abstract: Entry modes have impact on firms' performance in international markets. Using an organizational structural contingency perspective, we assert that firms with mechanistic structure can enhance their performance in international markets if they choose acquisitions as an entry mode. Mechanistic structure limits organizations' learning capability, which can be managed through acquisitions but not through other entry modes such as joint ventures. For managing limitations associated with the poor knowledge absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Recent studies on EMNCs highlight the fact that they may increase their value through international acquisitions because the firm can acquire tangible and intangible resources that are both difficult to acquire through market transactions and challenging to develop internally (Aybar & Ficici, 2009;Bhagat, Malhotra, & Zhu, 2011;Gubbi, Aulakh, Ray, Sarkar, & Chittoor, 2010). Furthermore, such value creation is greater when EMNCs enter developed markets, where target firms are more likely to carry higher quality resources and thus provide stronger complementarities to EMNC' existing capabilities (Agnihotri & Bhattacharya, 2018;Harrison, Hitt, Hoskisson, & Ireland, 2001). Harrison et al (2001) mention that the front-end, high-value skills, and resources available in developed markets, when combined with the low-cost, back-end capabilities in emerging markets, can generate highly valuable resource configurations to achieve higher market valuation and globalization.…”
Section: Institutional Distance and Emncs' Cba Eventsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies on EMNCs highlight the fact that they may increase their value through international acquisitions because the firm can acquire tangible and intangible resources that are both difficult to acquire through market transactions and challenging to develop internally (Aybar & Ficici, 2009;Bhagat, Malhotra, & Zhu, 2011;Gubbi, Aulakh, Ray, Sarkar, & Chittoor, 2010). Furthermore, such value creation is greater when EMNCs enter developed markets, where target firms are more likely to carry higher quality resources and thus provide stronger complementarities to EMNC' existing capabilities (Agnihotri & Bhattacharya, 2018;Harrison, Hitt, Hoskisson, & Ireland, 2001). Harrison et al (2001) mention that the front-end, high-value skills, and resources available in developed markets, when combined with the low-cost, back-end capabilities in emerging markets, can generate highly valuable resource configurations to achieve higher market valuation and globalization.…”
Section: Institutional Distance and Emncs' Cba Eventsmentioning
confidence: 99%
“…Recent works have explored the EMNC's engagement with the institutional complexity faced in the foreign markets (Agnihotri & Bhattacharya, 2018;Liu, Öberg, Tarba, & Xing, 2018;Muralidharan et al, 2017;Park, Meglio, Bauer, & Tarba, 2018). Research has shown postacquisition integration change over time and can lead to changes in the organizational identity.…”
Section: Corporate Name Change and Postacquisition Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Emerging market multinationals (EMMs) have received increasing attention in international business literature in the last two decades (Agnihotri & Bhattacharya, 2018;Buckley et al, 2014;Demirbag et al, 2009;Marchand, 2017;Luo, 1998;Panibratov et al, 2018;Sarapovas et al, 2016). Studies have shown that EMMs differ from developed market multinationals (DMMs) in a number of areas such as strategic flexibility (Luo & Rui, 2009), motivation for expansion (Luo & Tung, 2007), pace of internationalization (Dunning, 2006;Mathews, 2006), and firm specific advantages (Guillen & Garcia-Canal, 2009).…”
Section: Introductionmentioning
confidence: 99%